2021
DOI: 10.1111/jfpp.15267
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS analyses of volatile compounds of steamed breads fermented by Chinese traditional starter “Jiaozi” from different regions

Abstract: The volatile compounds of Jiaozi-steamed breads (JSBs) fermented by Jiaozi starters from eight regions in China were extracted using simultaneous distillation and extraction (SDE) and headspace solid-phase microextraction and determined using gas chromatography-mass spectrometry (GC-MS). 1-Hexanol, 3-methyl-1-butanol, phenylethyl alcohol, benzaldehyde, naphthalene, ethanol, acetic acid, and n-hexadecanoic acid were the main volatiles of JSBs. Principal component analysis exhibited that the volatiles of JSBs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It has been reported that phenylethyl alcohol was a typical metabolite of the Ehrlich pathway. Specifically, phenylalanine from flour was converted into phenylethyl alcohol by yeast through the Ehrlich pathway, and phenylethyl alcohol had a special odor of rose, honey, and sweet odor. , 2-Methyl-1-propanol and 3-ethyl-1-butanol are common odorants in CSBs, ,,,, which were, respectively, transformed from valine and leucine in flour and were typical products of the Ehrlich pathway . Compared with CF1318-CSB and CL10138-CSB, the FD values of 2-methyl-1-propanol (FD of 64) and 3-methyl-1-butanol (FD of 16) in CF1303-CSB are higher, indicating higher aroma intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that phenylethyl alcohol was a typical metabolite of the Ehrlich pathway. Specifically, phenylalanine from flour was converted into phenylethyl alcohol by yeast through the Ehrlich pathway, and phenylethyl alcohol had a special odor of rose, honey, and sweet odor. , 2-Methyl-1-propanol and 3-ethyl-1-butanol are common odorants in CSBs, ,,,, which were, respectively, transformed from valine and leucine in flour and were typical products of the Ehrlich pathway . Compared with CF1318-CSB and CL10138-CSB, the FD values of 2-methyl-1-propanol (FD of 64) and 3-methyl-1-butanol (FD of 16) in CF1303-CSB are higher, indicating higher aroma intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic aroma compounds and aroma profiles were different in sourdough-CSB and yeast-CSB, and ethyl lactate was only found in sourdough-CSB, which contributed to the floral odor . Interestingly, the volatile components of CSBs in North China and South China were different . CSBs made with different types of yeasts or yeast species showed similarity of the volatile compounds, while their composition and quantities were significantly different. , Aroma extraction methods solid-phase microextraction, simultaneous distillation-extraction, and purge and trap have been applied to the analysis of steamed bread flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Among the detected organic acids, linoleic acid with no obvious aroma can be further converted into aldehydes after oxidation (such as hexanal, trans‐ 2,4‐decadienal) 37‐39 . Additionally, n ‐hexadecanoic acid, as a good adsorbent of aroma components, brought the aroma of palm oil to noodles, but its high threshold value led to little contribution to food flavor 20 . Aldehydes were assumed to originate from lipid oxidation in flour 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Sample pretreatment and extraction SDE were conducted as described by Wang et al 20 with some modifications. Noodle samples (15 g) were placed into a round-bottom steaming flask and mixed with 100 mL of distilled water, then heated with an electric heating sleeve until boiling.…”
Section: Volatile Profiles Analysis Of Fwnsmentioning
confidence: 99%
See 1 more Smart Citation